2018
DOI: 10.1002/rcm.8218
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐isotope provenancing of archaeological skeletons including cremations in a reference area of the European Alps

Abstract: Gaussian mixture clustering is a promising method for the interpretation of multi-isotopic fingerprints aiming at detecting and quantifying migration and trade.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…[28][29][30][31][32][33][34][35][36]. Relevant to the present study, several new methodologies have been developed, which increase the accuracy of sex estimations [37][38][39][40][41], extend strontium isotope analyses to cremated materials, and verify the reliability of 87 Sr/ 86 Sr data on the petrous portion of the temporal bone [42][43][44][45][46][47][48][49]. In our study, we apply these new osteological methods and sampling strategies for the analysis of strontium isotopes to a sample of 29 burials from Szigetszentmiklós-Ü rgehegy, one of the most important and best-preserved cemeteries of the Late Nagyrév and Vatya culture.…”
Section: Plos Onementioning
confidence: 87%
“…[28][29][30][31][32][33][34][35][36]. Relevant to the present study, several new methodologies have been developed, which increase the accuracy of sex estimations [37][38][39][40][41], extend strontium isotope analyses to cremated materials, and verify the reliability of 87 Sr/ 86 Sr data on the petrous portion of the temporal bone [42][43][44][45][46][47][48][49]. In our study, we apply these new osteological methods and sampling strategies for the analysis of strontium isotopes to a sample of 29 burials from Szigetszentmiklós-Ü rgehegy, one of the most important and best-preserved cemeteries of the Late Nagyrév and Vatya culture.…”
Section: Plos Onementioning
confidence: 87%
“…This might, however, usually not be a necessary step when applying the feature ranking method, but serves as a validation tool for implementing the entropy‐based feature ranking described in this paper. Nevertheless, GMM cluster analysis was validated as a useful tool for the interpretation of multi‐isotope datasets, previously …”
Section: Discussionmentioning
confidence: 99%
“…We would, however, like to emphasize that a multi‐isotope approach is (usually) clearly recommended wherever possible. Recent studies demonstrated that the analysis and interpretation of multiple isotopic systems result in a gain of information compared with common bivariate analyse . Consequently, the exclusion of certain isotopic systems from analysis will result in a certain loss of information.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations